Indonesia Representasi Feminisme dalam Drama Netflix “The Glory Season 1” (Analisis Semiotika John Fiske) - Safitri, Dewi (LPPM Universitas Bina Sarana Informatika, 2023)
Mass media is an important tool for society to communicate and convey information. Mass media influence human attitudes and behavior, and have educational, influential, informational, and entertainment functions. Drama is a form of mass media that can raise social issues, including gender equality. Feminism is a movement that fights for gender equality, and drama often reflects feminist views. Korean dramas, such as K-Dramas, are very popular and often raise the issue of bullying and domestic violence, especially against women. Some dramas portray women as figures who only focus on their appearance, while others feature strong and brave women like Moon Dong-eun's character in